A Cultural Immersion Experience in Indonesia for U.S. Nursing Students. Issue 3 (June 2015) - Edwards, Joan E.
Abstract Cultural immersion experiences as part of the education of health care professionals are important as our global focus expands through technology, natural disasters, pandemics, wars and the mobility of the world population. This is the story of a recent cultural immersion experience to Indonesia by U.S. nursing students. Student groups each chose an Indonesian health topic for an in‐depth focus. Students critically evaluated published research and discussed evidence‐based practice ideas applicable to their selected health issues. Using this knowledge, they developed PICO posters for presentation at an international nursing conference in Indonesia. The students greatly valued their opportunity to experience a different culture firsthand and to spend time with Indonesian students and faculty.